THE RELATIONSHIP BETWEEN LOWER LIMB EXPLOSIVE POWER AND ABDOMINAL MUSCLE ENDURANCE ON SMASH VOLLEYBALL PERFORMANCE - Jannah, Laula Roikhatul; Fitriana Puspa Hidasari; Ali, Rizki Hazazi; Haetami, Mimi; Noviyanti, Noviyanti (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study is a correlational research. In line with the research objective, which is to examine the relationship between the variables being studied, this study focuses on the relationship between leg muscle explosive power and abdominal muscle endurance strength with smash hitting ability. Based on statistical analysis, a correlation was found between leg muscle explosive power and smash hitting ability. This is evident from the product moment correlation test (rₓ₁y) result of 0.689, indicating a significant relationship as the obtained r-value (0.689) is greater than the table value (0.514). Additionally, a significant relationship was found between abdominal muscle endurance strength and smash hitting ability, as shown by the product moment correlation test (rₓ₂y) result of 0.824. Therefore, there is a highly significant relationship, with the obtained r-value (0.824) greater than the table value (0.514). After obtaining the results of x₁y and x₂y, a multiple correlation test was conducted to assess the combined correlation. The results indicated that leg muscle explosive power and abdominal muscle endurance strength have a coefficient value in relation to smash hitting ability, as seen from the multiple correlation test (rₓ₁ₓ₂y) result of 0.84. Referring to the interpretation table for the r-value, the value of 0.84 indicates a very high correlation. Explosive power of the leg muscles and endurance strength of the abdominal muscles play a significant role in the performance of the smash ability